Effect of melatonin on the onset of puberty in male juvenile rats - Venugopal, Satya Prasad (Anat Cell Biol, 2019)
Melatonin or N-acetyl-5-methoxytryptamine, the fascinating molecule secreted by the pineal gland. Melatonin has a close interaction with hypothalamic-pituitary-gonadal axis. In non-seasonal breeders like rat its exact role in reproduction is controvertible. So it is worth to explore the possible role of melatonin on the onset of puberty in male albino rats. Two groups of male rats aged 5 and 10 days were used for the study. In each group, there were three subgroups, each receiving melatonin for 5 days, 10 days or till the day of descent of testes. Similar subgroups were used as controls. Without handling, animals were observed daily for the onset of puberty. On the day of descent of testes, body weight of the animal was noted, blood was collected, serum was separated and used for radio immunoassay. For histomorphometric analysis, all morphometric measurements were done using an occular micrometer. Volume fraction of seminiferous tubules, intertubular connective tissue of testes, cortex and medulla of thymus were estimated by point count method. In both the age groups melatonin advanced the age on descent of testes, increased the body weight, organ weight. It also increased the serum hormone levels. So, in conclusion this study indicates that exogenous melatonin advances the onset of puberty in male albino wistar rats and this effect is more pronounced in the younger animals.